2016
DOI: 10.1016/j.str.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Arm of the Human Papillomavirus Major Capsid Protein Is Immunogenic and Involved in Virus-Host Interaction

Abstract: SUMMARY Cervical cancer is the second most prevalent malignant tumor among women worldwide. High-risk human papillomaviruses (HPVs) are believed to be the major causative pathogens of mucosal epithelial cancers including cervical cancer. The HPV capsid is made up of 360 copies of major (L1) and 72 copies of minor (L2) capsid proteins. To date, limited high-resolution structural information about the HPV capsid has hindered attempts to understand details concerning the mechanisms by which HPV assembles and infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…Cryo-electron microscopy (cryo-EM) structures of the whole virus capsid have provided critical insight into the mechanism of HPV assembly ( 9 12 ), and crystal structures of the T = 1 L1-only VLP (HPV16) and L1 pentamers (HPV11, -16, -18, and -35) have illustrated how the HPV L1 monomer forms a canonical, eight-stranded β-barrel (BIDG-CHEF) joined by six highly variable loops (BC, CD, DE, EF, FG, and HI), five of which (all but CD) are located on the surface of the L1 pentamer ( 13 , 14 ). Biochemical and serological assays have further revealed that the neutralizing epitopes for HPV capsids are type restricted and mainly clustered on these six hypervariable loops of L1 ( 15 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cryo-electron microscopy (cryo-EM) structures of the whole virus capsid have provided critical insight into the mechanism of HPV assembly ( 9 12 ), and crystal structures of the T = 1 L1-only VLP (HPV16) and L1 pentamers (HPV11, -16, -18, and -35) have illustrated how the HPV L1 monomer forms a canonical, eight-stranded β-barrel (BIDG-CHEF) joined by six highly variable loops (BC, CD, DE, EF, FG, and HI), five of which (all but CD) are located on the surface of the L1 pentamer ( 13 , 14 ). Biochemical and serological assays have further revealed that the neutralizing epitopes for HPV capsids are type restricted and mainly clustered on these six hypervariable loops of L1 ( 15 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…4a–d , lower); this has been observed elsewhere for VLPs generated from different expression systems 35 , 39 , 40 . A comparison of the available density maps of all ten HPV types (plus HPV 59) 41 revealed structural differences in the diameters of the E. coli -generated HPV VLPs (HPV 6: 53.6 nm, HPV 11: 57.5 nm, HPV 16: 50.6 nm, HPV 18: 57.1 nm, HPV 31: 58.0 nm, HPV 33: 58.8 nm, HPV 45: 56.5 nm, HPV 52: 56.6 nm, HPV 58: 58.1 nm and HPV 59: 58.3 nm) (Fig. 4e ); this may be a consequence of the varied N-terminal truncations that would perhaps normally contribute to the interactions between capsomers during particle assembly 41 , 42 .…”
Section: Resultsmentioning
confidence: 99%
“…4f ), which may be possibly caused by the differences in particle homogeneity among the different types. The variance in the dataset sizes used in the reconstructions (~3,000 from 21,000 particles were selected to build a 6 Å HPV 59 VLPs cryoEM structures 41 , whereas only ~1000 particles were used in the final reconstruction of HPV 58 at 12.5 Å) might be another possibility to explain the resolution variance.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations